Source Apportionment and Risk Assessment of Heavy Metals in Soils During Dry and Rainy Seasons in Southern Malawi - Constance Chifuniro Utsale; Chikumbusko Chiziwa Kaonga; Fabiano Gibson Daud Thulu; Petra Chiipa; Stellah James; Ishmael Bobby Mphangwe Kosamu (Pollutants)
The recent increase in industrial activities has raised concerns regarding environmental quality in urban areas in Malawi. In this study, the contents of heavy metals [copper (Cu), zinc (Zn) and cadmium (Cd)] were analysed in 15 sites selected from Makata, Limbe, Maselema, Chirimba, and Maone industrial zones of Blantyre City in Malawi. Soil sampling was conducted during dry and rainy seasons, followed by laboratory analysis. The results revealed a few cases of elevated content of heavy metals exceeding permissible England and Canadian standards with higher content detected during the dry season than in the rainy season. Chirimba soil had the highest mean Zn content of 822 mg/kg in the rainy season and 579 mg/kg in the dry season. Maone soils had the highest Cd content, measuring 2.09 mg/kg in the rainy season and 3.06 mg/kg in the dry season. Chirimba soils also had the highest Cu content with levels of 105 mg/kg in the dry season and 79 mg/kg in the rainy season. The geo-accumulation index indicated that Zn posed the most severe pollution. The results of the Positive Matrix Factorisation model suggest that heavy metal pollution primarily originates from metal processing and manufacturing industries, followed by plastic manufacturing industries. This finding is supported by the nature of emissions from these sectors, where metal processing activities release heavy metals through particulates and waste to the environment, suggesting collective actions to prevent soil contamination.